Wikipedia Culture Gap: Quantifying Content Imbalances Across 40 Language Editions - Miquel-Ribé, Marc; Laniado, David (Frontiers in Physics, 2018)
The online encyclopedia Wikipedia is the largest general information repository created through collaborative efforts from all over the globe. Despite the project’s goal being to achieve the sum of human knowledge, there are strong content imbalances across the language editions. In order to quantify and investigate these imbalances, we study the impact of cultural context in 40 language editions. To this purpose, we developed a computational method to identify articles that can be related to the editors' cultural context associated to each Wikipedia language edition. We employed a combination of strategies taking into account geolocated articles, specific keywords and categories, as well as links between articles. We verified the method’s quality with manual assessment and found an average precision of 0.92 and an average recall of 0.95. The results show that about a quarter of each Wikipedia language edition is dedicated to represent the corresponding cultural context. Although a considerable part of this content was created during the first years of the project, its creation is sustained over time. An analysis of cross-language coverage of this content shows that most of it is unique in its original language, and reveals special links between cultural contexts; at the same time, it highlights gaps where the encyclopaedia could extend its content. The approach and findings presented in this study can help to foster participation and inter-cultural enrichment of Wikipedias. The datasets produced are made available for further research.